The Difference of Effectiveness Between Coconut Oil and Telon Wipes with Warm Water Baths in Preventing Hypothermia in Newborn Babies in PMB Ririn Restatiningrum, Bululawang. - sakinah, inge ayu wardani; Panggayuh, Ardi; Asworoningrum, Asworoningrum (Jurnal Keperawatan Terapan, 2020)
Newborns have not optimal thermoregulation system, but they sued for adaptation in the extrauterine so they can minimalize complications occur. If the conditions of not optimal ability in thermoregulation system does not compensated by the right baby care technique, it can cause hypothermia. This research intend to know the diffetence in effectiveness between coconut oil dan telon oil with warm bath in preventing hypothermia in newborn. This research use observational analytic with cross sectional approach as the research design with 30 samples that fullfil the inclusion criteria by purposive sampling. Data is processed using the Independent test t test and the results showed a p value of 0.196, which means that there was no difference in effectiveness between the husk of coconut oil and telon oil with a warm bath in preventing hypothermia in newborns. Based on the average temperature after treatment, coconut oil seka group has a higher average temperature so that it can be an alternative baby care.